THE INFLUENCE OF THE VOIDS ON AN ADHESIVE LAP JOINT: EXPERIMENTAL AND NUMERICAL ANALYSIS. (Journal of Sciences & Technology, 2018)
The aim of this paper is to present an experimental and numerical characterization, which is a typical adhesive for aerospace applications. This was done with two kinds of structures, with and without voids, and comparing their structural performance. Additionally, the X-RAY NONOTOM CT SCAN (computed tomography) has been used to determinate the distribution of the voids in the adhesive. Subsequently, numerical models, which represent experimental trials, were developed by modelling adhesives using the finite element technique. A shear test has been performed on the specimens in order to confirm the resistance of the bonded joint taking into account that the materials have the same mechanical characteristics. Then, the numerical simulation has been developed using the software ANSYS in order to analyze the adhesive lap joint model. The finite element displacement analysis of the single lap joint was examined for the cases with and without voids. The stress of the adhesive single-lap joints is mainly generated during the cooling process. The results between the experimental tests and the numerical model are in good agreement. In fact, it is noted that the numerical models have been shown to be very representative of experimental trials with reasonable maximum errors. Additionally, we have noted that the absence of the voids increase the stiffness of the lap joints with a reasonable percentage of the loads charges. In the absence of the voids, the load failure of the joint has been increased. However, the increase rate in the failure load changes depending on the structural features of the adhesive and the type of the adhesive.